The Influence of QRIS and E-Wallet Adoption on Transaction Efficiency and Profitability of MSMEs in Makassar City - Rahmawaty; Rachmawaty; Amraeni; Nursinah Amirullah; Ririn Mardhani Syakur (SEULANGA SYSTEM PUBLISHER, 2025)
This study aims to examine the influence of QRIS and e-wallet adoption on transaction efficiency and profitability of Micro, Small, and Medium Enterprises (MSMEs) in Makassar City. Digital payment systems are increasingly recognized as key drivers of business transformation, yet many MSMEs still rely heavily on cash-based transactions. Using a quantitative survey method, data was collected from 150 MSME respondents across various sectors including trade, culinary, and services. The research employed multiple linear regression analysis and Sobel test to evaluate both direct and indirect effects. The results demonstrate that QRIS adoption significantly improves transaction efficiency by accelerating payment processes, reducing cash-handling costs, and minimizing recording errors. Similarly, e-wallet adoption has a positive effect on transaction efficiency by offering flexibility and convenience to customers, thereby strengthening MSME competitiveness. Transaction efficiency itself has the strongest effect on profitability, indicating that operational improvements directly translate into higher revenues and profit margins. In addition, both QRIS and e-wallet adoption exhibit direct positive effects on profitability, showing that digital payments not only enhance efficiency but also attract more customers and expand sales opportunities. Still, the analysis confirms that transaction efficiency mediates the relationship between adoption and profitability, suggesting that efficiency gains are a crucial mechanism through which digital payments improve financial outcomes. These findings highlight the strategic role of digital payments in enhancing MSME performance and provide valuable implications for policymakers, financial institutions, and service providers to accelerate financial inclusion and digital transformation among MSMEs in Indonesia.